Challenges in Diagnosing Attention-Deficit Hyperactivity Disorder in Adults - Underdiagnosed, Misdiagnosed, or Overdiagnosed: a Case Report - Kostić, Milutin; Mehmedović, Amin (Medical Word, 2026)
Attention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder that is sometimes undiagnosed, misdiagnosed, or overdiagnosed, particularly in adults. Although ADHD is typically diagnosed in childhood, its symptoms often persist into adulthood, complicating diagnosis, especially in women. The aim of this case report was to highlight the challenges in diagnosing ADHD in adults. We present a 30-year-old woman with a complex psychiatric history, in whom the diagnosis of ADHD was considered in adulthood. Initially diagnosed with depression and borderline personality disorder, her symptoms of lack of motivation and poor concentration persisted for over a decade. Despite various psychiatric approaches, her functioning remained impaired. After the latest treatment attempts, her symptoms, including impulsivity, showed partial improvement, but her prognosis remains uncertain. The diagnosis of ADHD in adults should be approached with caution, considering the risks of underdiagnosis, misdiagnosis, and overdiagnosis, especially in patients with overlapping symptoms of other mental health disorders.
Keywords: attention-deficit hyperactivity disorder in adults; diagnostic challenges; suicide attempt